(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Relevance. The results of performances at the World and European Championships, as well as the Olympic Games of the Russian men’s and women’s national handball teams over the past 30 years are impressive. A high level of achievements over a long period would have been impossible without the preparation of a full-fledged reserve for the national teams of the country. To a greater extent, the successful breeding work was successful for the Russian women’s national team, whose highest achievements occurred in the two thousandth years. The further progress of Russian handball players is conditioned by the development and application of modern effective training techniques in the process of sports training, which increase the ability of players to successfully compete in major tournaments, winning prizes and medals for their clubs and national teams.